The vocational Adjustment of workers according to the analysis of job and design ((Local Research in the technology al information and communication office in the parliament)) - الزيدي, ناظم جواد; محمد, محمد جابر (Journal of Economics and Administrative Sciences, 2016)
AbstractThe purpose of the present paper is to light on the relationship between jobs design, analysis and its reflections on reinforcing workers' vocational adjustment. The present paper aims to accomplish cognitive and applied goals, top of which, test of functional analysis ability to have effect upon workers' vocational adjustment via job design directly and indirectly owning to the virtual factor practiced by these practices on the sought organization. The problem of the present paper comes with many, the most important is the of how to bolster and back up worker's technical adjustment through good and accurate design for the job. Based on this problem and goals as to explain the nature of relationship between  the research's  main and sub-main variables, it has been prepared five basic hypotheses, where it has been employed  questionnaire  as a tool for collecting information and data  supported by personal texts . have been prepared based on a number of ready scales by relying on fifth grading; the scales have been subjected to consistence and reliability scales that being distributed on a sample of 72 of Information Technology and Communications.